(3S,4Z)-3-Chloro-1-methyl-4-[(2E)-(3-methylbenzylidene)hydrazinylidene]-3,4-dihydro-1H-2,1-benzothiazine 2,2-dioxide - Muhammad Shafiq; M. Nawaz Tahir; Islam Ullah Khan; Muhammad Zia-Ur-Rehman (Acta Crystallographica Section E, 2012)
In the title compound, C17H16ClN3O2S, the dihedral angle between the benzene rings is 7.75 (13)°. The thiazine ring adopts an envelope conformation with the S atom as the flap at a distance of 0.813 (2) Å from the plane through the other five atoms. In the crystal, C—H...O hydrogen bonds link the molecules into chains propagating in [100].